2001
DOI: 10.1109/7361.983471
|View full text |Cite
|
Sign up to set email alerts
|

Ozone sensing using In/sub 2/O/sub 3/-modified Ga/sub 2/O/sub 3/ thin films

Abstract: It is shown that at elevated temperatures the conductance of anIn 2 O 3 -modified Ga 2 O 3 thin film depends significantly and reversibly on the ozone concentration in the ambient air. This ozone sensitivity is much greater than with pure Ga 2 O 3 or In 2 O 3 thin films, respectively. The ozone sensitivity of the In 2 O 3 -modified Ga 2 O 3 thin film is characterized by an impressive selectivity, and is maximal at an operation temperature of about 600 C. The cross sensitivities to other gases present in ambien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…Unfortunately, the values of and are not constant for various sensors. For example, in the literature on , one can find that values have varied from 0.2 to 1.5 [50,55,123,124]. Experimental studies and phenomenological modeling have shown that the power exponent can, in principle, be derived from the mass action laws and rate constants of the respective surface reactions and the relationship between the sensor resistance and the trapped charge density of chemisorbed species [25][26][27][125][126][127].…”
Section: General Characterization Of In 2 O 3 -And Sno 2 -Based Condumentioning
confidence: 99%
“…Unfortunately, the values of and are not constant for various sensors. For example, in the literature on , one can find that values have varied from 0.2 to 1.5 [50,55,123,124]. Experimental studies and phenomenological modeling have shown that the power exponent can, in principle, be derived from the mass action laws and rate constants of the respective surface reactions and the relationship between the sensor resistance and the trapped charge density of chemisorbed species [25][26][27][125][126][127].…”
Section: General Characterization Of In 2 O 3 -And Sno 2 -Based Condumentioning
confidence: 99%
“…Surface properties are influenced by new boundaries between grains of different chemical composition. It is anticipated that all of these phenomena will contribute advantageously to the gas sensing mechanism (Zakrzewska 2001) The use of mixed oxides in gas detection has been successfully implemented (Frank et al 2001;Galatsis et al 2001aGalatsis et al , b, 2002Gurlo et al 1998;Li et al 2001). In general, an increase in doping concentration leads to an increase in conductivity due to the higher concentration of carriers available for conduction.…”
Section: Introductionmentioning
confidence: 97%
“…In recent years, more and more attention has been paid to Ga 2 O 3 because of its superior properties such as a wide band gap (∼5.0 eV) and a high Baliga’s figure of merit (BFoM). That enables Ga 2 O 3 to be a versatile material for solar blind ultraviolet (UV), X-ray photodetectors, power devices, biological agent sensors, and gas monitors. , Specially, Ga 2 O 3 has been regarded as a promising candidate for reproducible gas detection due to its high stability and low power consumption, for gases such as O 2 , CO, H 2 , and ozone. Ga 2 O 3 bulk crystals and nanostructures usually exhibit better gas sensing performance in contrast to the thin-film counterparts, , owing to their low resistance or large specific surface area. On the other hand, thin-film devices having the advantages of low cost, being lightweight, easy integration, and good reproducibility are more desirable for practical applications.…”
Section: Introductionmentioning
confidence: 99%